“Traduttori-traditori”: pasajes de traducción en busca de una casuística (El Hilo de la Fabula, 2022)
This article aims to give a brief overview of errors and successful choices in translations of Spanish literary works into Italian. The examples are useful as a first step to establish rules to support and protect the task of literary translation, which is becoming increasingly necessary in contemporary culture. A number of specific examples show the traps into which several translators, including experts, have fallen, and on the other hand, some show excellent solutions of expressions that are very difficult to transfer to another language. As a result, some rules have arised: the translator must perfectly know the source language and the target language, with their geographical and colloquial variations. Also, he must be very well informed about the historical-cultural and social context of the work he is going to translate, in order to reproduce the internal messages correctly without falling into misinterpretations.
Keywords: Literary translation; Italian; Spanish; false friends; gender errors; local color; historical context; cultural context